Histone-like nucleoid-structuring protein (H-NS) regulatory role in antibiotic resistance in Acinetobacter baumannii - Rodgers, Deja (2021)
Fil: Fil: Rodgers, Deja. California State University Fullerton. College of Natural Sciences and Mathematics. Department of Biological Science. Center for Applied Biotechnology Studies; United States.